2007
DOI: 10.1002/ibd.20220
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical results of ileocecal resection for Crohnʼs disease

Abstract: Long-term outcomes for ileocecal resection in CD are excellent with 48% of patients remaining symptom-free and only 35% requiring repeat resection surgery at 10 years. This should be borne in mind when considering biologic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 14 publications
2
46
1
10
Order By: Relevance
“…Bernell et al [5] observed that postoperative recurrence occurred in 33% and 44% of patients at 5 and 10 years after resection, respectively. Similar to these results, Cullen et al [11] observed that the relapse rate was 35%. The relapse rate was relatively low in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Bernell et al [5] observed that postoperative recurrence occurred in 33% and 44% of patients at 5 and 10 years after resection, respectively. Similar to these results, Cullen et al [11] observed that the relapse rate was 35%. The relapse rate was relatively low in our study.…”
Section: Discussionsupporting
confidence: 72%
“…The mean age was 38.13 years in our study. Whereas in the Western countries, the mean age was reported to be 32 years [5] and 28.7 years [11] . The average age of surgery from most reports in Western countries is lower than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Alkalmazott immunmoduláns és biológiai kezelés, sebészeti beavatkozások gyakorisága, valamint aktivitási indexek az egyéves kontroll idején [6,15,16]. Freeman és munkatársai 1015 CD-s beteg adatait elemezték, az átlagos követési idő több mint 10 év volt, és 247 betegnél találtak granulomát.…”
Section: Táblázatunclassified
“…Cullen és munkatársai 139, ileocaecalis reszekción átesett felnőtt beteg 48%-ában találtak granulomát. A granulomás csoportban a relapsusok és az ismételt reszekciós műtétek szignifi kánsan gyakoribbak voltak [15]. Markowitz és munkatársai 56 gyermek CD-s kö-vetése során szintén gyakoribbnak találták a műtéti beavatkozások szükségességét a granulomás csoportban [8].…”
Section: Táblázatunclassified
“…1, 2), early resection can produce the same mucosal healing one expects to achieve with aggressive medical therapy. However, the recurrence-free interval is likely to be longer (as demonstrated by studies of patients who have undergone surgery relatively early for acute presentations or for early onset perforation) [24,25]. Early surgical intervention in patients with B1 disease and short-segment lesions allows one to perform simple procedures, which can be carried out with minimally invasive techniques and without the increased risk of complications (postoperative infections in particular) associated with surgical treatment of more complex disease (B3) (Fig.…”
Section: Epidemiologymentioning
confidence: 99%